SYMPATHOADRENAL PLACE IN DEVELOPMENT OF IGNITION AND MODERN UNDERSTANDING OF THE MECHANISM OF THEIR INTERACTION - S. Pavlovsky; A. Svintsitskyi; M. Taranenko (Bogomolets National Medical University, 2015)
Summary. Naturally, any contact with a foreign agent of the body considers as a stress. Thus, in the process of exogenous or endogenous stimulation ultimately the activation sympathoadrenal system, components whose main players are catecholamines. A key component of these substances is modulated nuclear transcription factor function and the synthesis of proinflammatory cytokines. Currently, the growing interest in antiinflammatory properties [32-agonists [49,67,80]. Thus, the experimental model thymus proved that sympathoadrenal system may affect T cells not only through direct effects on P2-adrenergic receptors of T lymphocytes, but also indirectly, through its impact on p2-adrenoreceptornal system thymic epithelial cells, by raising intracellular c- AMP. Activate sympathoadrenal system, such as acute stress, leads to an increase in the number of natural killer cells in the periphery and the growth of their activity, toxicity, decreased proliferation. Result sympathoadrenal interactions and immune systems largely depends on the maturity of the immune system at the time the action it adrenergic agent. The function of natural killer cells, as well as other cells of the immune system is modulated by the sympathic division of the autonomic nervous system, with this modulation is strictly specific. Adrenergic receptors, natural killer cells are very sensitive to changes in blood concentrations of catecholamines. Thus, increasing the concentration of adrenaline causes selective reduction in density and a1- p2-receptors, while receptors density a2 unchanged. Adequate response of the immune system are possible only as a result of physiological stress. While the continued tension hypothalamus-pituitary-adrenal system leads to distortion of immune functions, until the development of autoimmune reactions. All this is a clear indication of the involvement of the autonomic nervous system in the pathogenesis of rheumatic diseases.